Analisis Noise Floor Threshold Terhadap Signal Strength Pada Wireless Local Area Network Protokol Nv2 - Juwari Juwari; Moch Yusuf Asyhari (Journal of Information System Research (JOSH), 2022)
Data transmission media using wireless is currently an alternative to using wired transmission media. Wireless Local Area Network (WLAN) used so far uses 2.4 GHz and 5 GHz frequencies. The use of frequency in the IEEE 802.11 standard protocol is increasingly dense and prone to interference. So that various protocols began to be developed according to needs. In this study using a frequency of 5 GHz and the Nv2 protocol. One of the protocol features in the Mikrotik Wireless device. Signal strength is affected by the Noise Floor Threshold. Noise Floor Threshold value -128 to -110. The higher the Noise Floor Threshold value, the weaker the signal strength will be. The lower the Noise Floor Threshold value, the stronger the signal strength. The Noise Floor Threshold value will also affect the Signal To Noise (dB). When the Noise Floor Threshold value is low, the Signal To Noise (dB) strength is getting stronger, and vice versa